Tritium-labeled (E,E)-2,5-bis(4′-hydroxy-3′-carboxystyryl)benzene as a probe for β-amyloid fibrils - Matveev, Sergey V.; Kwiatkowski, Stefan; Sviripa, Vitaliy M.; Fazio, Robert C.; Watt, David S.; LeVine, Harry (Bioorganic & medicinal chemistry letters, 2014)
Accumulation of amyloid-β plaque and tau tangle pathologies in Alzheimer’s disease occurs over an extended time-frame, and the early detection and prevention of their formation are active research foci. Tritiated (E,E)-1-[3H]-2,5-bis(4′-hydroxy-3′-carbomethoxystyryl)benzene possesses an improved level of chemical stability relative to a previously reported radioiodinated analog for detecting and quantifying Aβ and tau pathology in brain tissue and in studies of in vitro assembled Aβ and tau. [Display omitted] Accumulation of Aβ in the brains of Alzheimer disease (AD) patients reflects an imbalance between Aβ production and clearance from their brains. Alternative cleavage of amyloid precursor protein (APP) by processing proteases generates soluble APP fragments including the neurotoxic amyloid Aβ40 and Aβ42 peptides that assemble into fibrils and form plaques. Plaque-buildup occurs over an extended time-frame, and the early detection and modulation of plaque formation are areas of active research. Radiolabeled probes for the detection of amyloid plaques and fibrils in living subjects are important for noninvasive evaluation of AD diagnosis, progression, and differentiation of AD from other neurodegenerative diseases and age-related cognitive decline. Tritium-labeled (E,E)-1-[3H]-2,5-bis(4′-hydroxy-3′-carbomethoxystyryl)benzene possesses an improved level of chemical stability relative to a previously reported radioiodinated analog for radiometric quantification of Aβ plaque and tau pathology in brain tissue and in vitro studies with synthetic Aβ and tau fibrils.